Privacy paradox among romantic couples: the use of location sharing apps - Lin, Chia Shin (Frontiers in Human Dynamics, 2025)
The proliferation of smartphones has elevated privacy concerns, particularly regarding the easy access to geolocation information. Scholars have attempted to find a balance between location sharing and privacy protection; however, such a balance seems less relevant in the use of location-sharing apps among romantic couples. This study aims to explore the role of location-sharing apps in romantic relationships and examines whether privacy still matters in this context. The couple and family technology framework as well as sociotechnological family framework were incorporated to develop a theoretical framework for the current study. A survey was applied and the sample size was 434. The findings reveal that acceptance of monitoring negatively associates with perceived intrusion while scope positively associates with perceived intrusion. Scope is positively associated with mate-guarding. Perceived intrusion negatively associates with relationship satisfaction whereas mate-guarding positively associates with relationship satisfaction. Theoretical implications were discussed.